Validation of the Parkinson’s Disease Caregiver Burden Questionnaire in Progressive Supranuclear Palsy - Martin Klietz; Hannah V. Eichel; Selma Staege; Anna Kutschenko; Gesine Respondek; Meret K. Huber; Stephan Greten; Günter U. Höglinger; Florian Wegner (Parkinson's Disease)
Progressive supranuclear palsy (PSP) is an atypical Parkinson syndrome with axial akinetic-rigid symptoms, early postural instability, and ocular motor impairments. Patients experience a rapid loss of autonomy and care dependency; thus, caregivers must assist in the activities of daily living early in the course of the disease. Caregiver burden is an extremely important factor in disease management. However, there are no specific questionnaires for assessment of caregiver burden in PSP. This study aims to validate the Parkinson’s disease caregiver burden questionnaire (PDCB) as a specific measure of caregiver burden in PSP. PSP patients were assessed by the PSP rating scale, PSP quality-of-life questionnaire (PSP-QoL), Montreal cognitive assessment test (MoCA), and geriatric depression scale (GDS-15). Caregivers filled out the short form 36-health survey, GDS-15, PDCB, and the caregiver burden inventory (CBI). 22 patient caregiver pairs completed the study. PDCB showed a highly significant correlation with the CBI (r 0.911; p<0.001). Internal reliability of the PDCB measured by Cronbach’s alpha was favourable at 0.803. These data support the specificity of the PDCB in PSP caregivers. Future studies with larger sample sizes of PSP patients and caregivers and a multicentric longitudinal design should be performed to gain further insight of caregiver burden in PSP.